POTENSI RETRIBUSI PASAR UMUM DI KOTA BENGKULU - Ahmad Soleh (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
Ahmad Soleh, Wagini, Vero Agustin; Market Levy is a charge withdrawn by the Department of Industry and Trade to compulsory retribution for the use of facilities in the form of stalls, kiosks and courtyards provided by the city government of Bengkulu. This study aims to examine the potential of public market retribution in Bengkulu City. Data collection techniques in this study using documentation. Secondary data was obtained from the Office of Industry and Trade of Bengkulu City. The market retribution potential formula is used in this method of study. The results showed that the existing market potential in Bengkulu City fluctuated. The average potential of general market retribution is Rp 2,220,464,960 per year with an average growth of 2.51% per year. This is in line with the realization of public market levies that also experience fluctuations. The average realization of general market retribution revenue amounted to Rp 1,854,906,535, - with an average growth of 6.53% per year. The percentage of realization achievement of potential revenue of general market retribution in Bengkulu city from 2014 to 2016 were 82.08%, 80.23% and 88.07% respectively with an average of 83.53% per year. Achievement average achievement above 80% is considered good. However, the local government of Bengkulu city should always try to increase the realization of acceptance of public market retribution with its potential.Key Words: Potential, Public Market Levy, Bengkulu City.